Fungal Diversity and Heavy Metal Mycoremediation Potential of Military Shooting Range Soils in Kaduna State, Nigeria - Ibrahim Yusuf Tafinta; Khadija Abdullahi Yarima; Mu’awiyya Umar Ladan; Umar Balarabe Ibrahim (Darul Yasin Al Sys, 2026)
Military shooting ranges are significant point sources of heavy metal contamination that may alter soil microbial communities and ecological functioning. Given the ecological roles and metal-tolerance mechanisms of soil fungi, this study investigated fungal diversity in soils from the Jaji Military Shooting Range, Kaduna State, Nigeria, and examined the relationship between fungal abundance and selected heavy metal concentrations. Soil samples were collected from five locations at a depth of 0–15 cm. Cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb) concentrations were determined by Flame Atomic Absorption Spectrophotometry following tri-acid digestion. Fungi were isolated through serial dilution, cultured on Potato Dextrose Agar, identified morphologically, and evaluated using Simpson’s Diversity Index. Data were analyzed using analysis of variance and Pearson correlation analysis at a 5% significance level. Lead had the highest recorded concentration, reaching 43.61 mg/kg at location B, while all metals exhibited significant spatial variation (p < 0.05). Eleven fungal species, predominantly belonging to Ascomycota and Mucoromycota, were identified. Mucor racemosus (35.59%) and Aspergillus niger (22.88%) were the most prevalent isolates. A Simpson’s Diversity Index of 0.8 indicated high species diversity and relative community evenness. Pearson correlation coefficients (r = 0.268–0.329) showed weak, nonsignificant positive relationships between fungal abundance and heavy metal concentrations. These findings demonstrate that metal-impacted shooting-range soils support a diverse and resilient fungal community. The persistence and prevalence of indigenous fungi under metal stress highlight their ecological adaptability and identify them as promising candidates for further evaluation in heavy metal mycoremediation strategies.